REVIEWING AL-QAEDA'S INFILTRATION IN INDONESIA: A HISTORICAL REFLECTION - Sahrasad, Herdi; Syukur, Yanuardi; Tabrani, Dedy; Chaidar, Al (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2019)
Al-Qaeda's infiltration into the Southeast Asian region is inseparable from the existence of Jamaah Islamiyah (JI). Some Jamaah Islamiyah cadres are veterans of the Afghanistan War. Historically Al-Qaeda under the leadership of Osama Bin Laden has trained the military skills of Jamaah Islamiyah cadres to help the Afghan jihadists fight Soviet communism until the Soviets defeated and left Afghanistan. Then Al-Qaeda succeeded in entering Indonesia through the Jamaah Islamiyah network and its cells in Southeast Asia by mobilizing key actors and radical actions. In Indonesia, Jamaah Islamiyah with the support of Al-Qaeda succeeded in carrying out a series of bomb attacks including Bali Bomb (2002), Kuningan Bomb (2004), JW Marriot and Ritz-Carlton Bomb Jakarta (2009). The strategy of the Al-Qaeda movement in Indonesia does not appear openly by forming an underground organization (clandestine). Its existence exists but in the form of a Formless Organization (OTB) for the security of its organization. Their infiltration through these networks has succeeded in bringing in their radical ideology and movements in Indonesia in particular and in the Southeast Asian region in general.